THE USE OF IDENTIFICATION METHODS FOR ESTIMATING THE PARAMETERS OF BENDING OSCILLATIONS OF THE CAR BODY - Liapshyn, K. M.; Vuchetych, I. I.; Klokov, O. V.; Baltskaps, P. Ya. (Science and Transport Progress, 2008)
The description of the developed method of vibration tests with the subsequent data processing is given.